TNF blockade contributes to restore lipid oxidation during exercise in children with juvenile idiopathic arthritis - Emmanuelle Rochette; Pierre Bourdier; Bruno Pereira; Eric Doré; Anthony Birat; Sébastien Ratel; Stéphane Echaubard; Pascale Duché; Etienne Merlin (BMC, 2019)
Abstract Background Children with juvenile idiopathic arthritis (JIA) have impaired physical abilities. TNF-α plays a crucial role in this pathogenesis, but it is also involved in the use of lipids and muscle health. Objective of this study was to explore substrate oxidation and impact of TNF blockade on energy metabolism in children with JIA as compared to healthy children. Methods Fifteen non-TNF-blockaded and 15 TNF-blockaded children with JIA and 15 healthy controls were matched by sex, age, and Tanner stage. Participants completed a submaximal incremental exercise test on ergocycle to determine fat and carbohydrate oxidation rates by indirect calorimetry. Results The maximal fat oxidation rate during exercise was lower in JIA children untreated by TNF blockade (134.3 ± 45.2 mg.min− 1) when compared to the controls (225.3 ± 92.9 mg.min− 1, p = 0.007); but was higher in JIA children under TNF blockade (163.2 ± 59.0 mg.min− 1, p = 0.31) when compared to JIA children untreated by TNF blockade. At the same relative exercise intensities, there was no difference in carbohydrate oxidation rate between three groups. Conclusions Lipid metabolism during exercise was found to be impaired in children with JIA. However, TNF treatment seems to improve the fat oxidation rate in this population. Trial registration In ClinicalTrials.gov, reference number NCT02977416, registered on 30 November 2016.